A Cold Rain on the Parade When the Sámi Celebrate 100th Anniversary - Ravna, Øyvind (Arctic Review on Law and Politics, 2017)
Source at: https://dx.doi.org/10.23865/arctic.v8.684 6 February 2017 marks the centenary of The First Sámi Congress, which is also the reason that we today celebrate the 6th of February as the Sámi National Day. The First Congress will be thoroughly celebrated in Trondheim where it originally took place. Such an anniversary naturally inspires reflection on what the Sámi have achieved in the years since Elsa Laula Renberg and other visionary Sámi leaders organized the Trondheim meeting in 1917 to discuss how to safeguard Sámi interests and their future during the most difficult period of the Norwegianisation policy. Much has been achieved in these intervening years. The Sámi have obtained a constitutional amendment that protects Sámi language, culture and ways of life, a Sámi Act and a Sámi Parliament. Norway has also ratified ILO Convention no. 1691 and adopted the Finnmark Act,2 thereby recognizing that the Sámi constitute an indigenous people who have the right to own their ancestral lands. But there are still dark rain clouds hanging over the Sámi horizon.